Sensorless Predictive Direct Power Control PDPC_SVM For PWM Converter Under Different Input Voltage Conditions - Ismail Boukhechem; Ahcen Boukadoum; Lahcene Boukelkoul; Houssam Eddine Medouce (IAES Indonesian Section, 2020)
In this paper, a new virtual flux (VF) based predictive direct power control (VF_PDPC) applied for three-phase pulse width modulation (PWM) rectifier is proposed. The virtual flux estimation is performed using a pure integrator in series with a new adaptive algorithm in order to cancel dc offset and harmonic distortions in the estimated VF. The introduced structure is able to produce two virtual flux positive sequence components orthogonal output signals under unbalanced and distorted voltage conditions. The main features of the proposed virtual flux estimator are, it's simple structure, accuracy, and fast VF estimation over the excited integrators. Therefore, the estimated VF is then used for robust sensorless VF-PDPC with a constant switching frequency using space vector modulation (SVM) and tested through numerical simulations. The instantaneous active and reactive powers provided by orthogonal (VF) positive sequence components are directly controlled. More importantly, this configuration gives quasi-sinusoidal and balanced current under different input voltage conditions without using the power compensation methods. The results of the simulation confirmed the validity of the proposed virtual flux algorithm and demonstrated excellent performance under different input voltage conditions, complete rejection of disturbances.